2024
DOI: 10.1073/pnas.2307633121
|View full text |Cite
|
Sign up to set email alerts
|

Observation of negative surface and interface energies of quantum dots

Jason J. Calvin,
Amanda S. Brewer,
Michelle F. Crook
et al.

Abstract: Surface energy is a fundamental property of materials and is particularly important in describing nanomaterials where atoms or molecules at the surface constitute a large fraction of the material. Traditionally, surface energy is considered to be a positive quantity, where atoms or molecules at the surface are less thermodynamically stable than their counterparts in the interior of the material because they have fewer bonds or interactions at the surface. Using calorimetric methods, we show that the surface en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Furthermore, the CNT model neglects surface chemistry, chemical reactions and oxidation state alterations, which often exert significant control over the nucleation process . Moreover, recent experiments have suggested that the surface energy may be negative, indicating that CNT could be entirely inappropriate . Although other physical theories such as spinodal decomposition, kinetic theory and quantum-mechanical correction methods have been proposed, the field of nonclassical nucleation of NPs remains relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the CNT model neglects surface chemistry, chemical reactions and oxidation state alterations, which often exert significant control over the nucleation process . Moreover, recent experiments have suggested that the surface energy may be negative, indicating that CNT could be entirely inappropriate . Although other physical theories such as spinodal decomposition, kinetic theory and quantum-mechanical correction methods have been proposed, the field of nonclassical nucleation of NPs remains relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…27 Moreover, recent experiments have suggested that the surface energy may be negative, indicating that CNT could be entirely inappropriate. 28 such as spinodal decomposition, 29 kinetic theory 30 and quantum-mechanical correction methods 31 have been proposed, the field of nonclassical nucleation of NPs remains relatively unexplored.…”
Section: ■ Introductionmentioning
confidence: 99%